2005
DOI: 10.1111/j.1475-3588.2005.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Justifiable Psychopharmacology or Overzealous Prescription? Examining Parental Reports of Lifetime Prescription Histories of Psychiatrically Hospitalised Children

Abstract: Background:  This research investigated parent reports of pre‐admission psychotropic medication histories of psychiatrically hospitalised children in the United States. The emphasis was on identifying factors related to potentially overzealous medication use. Method:  Diagnosis, insurance type, and demographics for 170 consecutive admissions were assessed via research case conference and chart review. An extreme group of children with lengthy medication histories (n = 20) was also identified, and prescription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Some research has examined the use of two concomitant medications, but studies have not examined the use of more than four medications prescribed simultaneously. In fact, several authors have expressed concern over the “excessive and indiscriminate use of psychotropic medications in children” (Behr, 1998, p. 900; Dean, McDermott, & Marshall, 2006; Zakriski, Wheeler, Burda, & Shields, 2005). Woolston (1999) suggested that although combined pharmacotherapy is “the optimal therapeutic intervention for some children” (p. 1456), often the prescribing physician must make a “risk–benefit analysis in the absence of sufficient scientifically validated data” (p. 1456).…”
Section: Discussionmentioning
confidence: 99%
“…Some research has examined the use of two concomitant medications, but studies have not examined the use of more than four medications prescribed simultaneously. In fact, several authors have expressed concern over the “excessive and indiscriminate use of psychotropic medications in children” (Behr, 1998, p. 900; Dean, McDermott, & Marshall, 2006; Zakriski, Wheeler, Burda, & Shields, 2005). Woolston (1999) suggested that although combined pharmacotherapy is “the optimal therapeutic intervention for some children” (p. 1456), often the prescribing physician must make a “risk–benefit analysis in the absence of sufficient scientifically validated data” (p. 1456).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical trials described herein, however, are the only recent randomized clinical trials directly comparing each of them. This is not to say that psychopharmacologic treatment is without controversy in that adverse side effects, inadequately trained physicians, variability in referrals, direct marketing of pharmaceuticals, and complex diagnostic dilemmas all contribute to a note of caution whenever psychopharmacologic treatment is involved (Kravitz et al, 2005;Riba & Balon, 2005;Ringold, 2005;Varley, 2004;Williams, Klinepeter, Palmes, Pulley, & Meschan Foy, 2004;Zarkiski et al, 2005). Note also that the conclusions from these treatments should not be generalized to other medications or to children with other diagnoses who may exhibit attention or behavioral diffi culties.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of a systematic review of antipsychotics in early onset schizophrenia conclude that the poor quality of studies of atypical medications ''is an alarming situation since the use of antipsychotic medications in children and adolescents has increased recently in the absence of a scientific database'' (Armenteros & Davies, 2006, p. 146). In addition, given the current managed care climate in the United States in which services can be fragmented, psychiatrists limit their practice to medication management, and primary care physicians prescribe a majority of psychotropic medications for youth, the risk for overmedication has increased (Zakriski, Wheeler, Burda, & Shields, 2005). In reviewing the extant literature, the APA Working Group on Psychoactive Medications for Children and Adolescents (2006) concluded that Most of the evidence for efficacy is limited to acute symptomatic improvement, with only limited attention paid to functional outcomes, long-term durability, and safety of treatments.…”
Section: Psychotropic Medication With Childrenmentioning
confidence: 99%